2013
DOI: 10.1371/journal.pone.0080053
|View full text |Cite
|
Sign up to set email alerts
|

Lin28B Is an Oncofetal Circulating Cancer Stem Cell-Like Marker Associated with Recurrence of Hepatocellular Carcinoma

Abstract: By using an expressed sequence tag bioinformatic algorithm, we identified that Lin28 homolog B (Lin28B) may have an oncofetal expression pattern which may facilitate detecting cancer cells in adults. It is also reported to be a potential marker for cancer stem cells. Therefore, we sought to verify oncofetal-stemness characters of Lin28B and test its potential as a circulating cancer stem cell-like marker in adult HCC patients. Lin28B mRNA was examined in a panel of fetal tissue, adult tissue and tumors. Lin28B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…However, this study demonstrated a novel mechanism, indicating that activation of IKKb, an inflammatory kinase in the NF-kB pathway, was strongly correlated with the expression of stemness genes, especially LIN28B in human breast cancer cell lines or tissues. Previous studies also showed that LIN28B promoted tumor cell transformation (23,24) and had a functional role in the maintenance of CSCs (25,26). Consistent with these findings, our experiment results showed that expression of LIN28B was highly positively correlated with tumor progress in human breast cancer patients, indicating that there were high levels of LIN28B in stage 3 patients with lymphatic metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, this study demonstrated a novel mechanism, indicating that activation of IKKb, an inflammatory kinase in the NF-kB pathway, was strongly correlated with the expression of stemness genes, especially LIN28B in human breast cancer cell lines or tissues. Previous studies also showed that LIN28B promoted tumor cell transformation (23,24) and had a functional role in the maintenance of CSCs (25,26). Consistent with these findings, our experiment results showed that expression of LIN28B was highly positively correlated with tumor progress in human breast cancer patients, indicating that there were high levels of LIN28B in stage 3 patients with lymphatic metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, it has been reported that LIN28A/LIN28B can promote transformation by repressing let-7 miRNAs, and that activation of LIN28A/LIN28B occurs in many different human tumors with a frequency of approximately 15% (23,24). Recent studies have also suggested that LIN28 plays an important role in the maintenance of CSCs (25,26) and Wnt signaling could directly activate LIN28 to augment breast cancer stem cell expansion (27).…”
Section: Introductionmentioning
confidence: 99%
“…LIN28A and LIN28B function as oncoproteins that promote cell proliferation and transformation (25). LIN28A/LIN28B expression has also been found in diverse malignancies and is associated with decreased survival in ovarian, colon and hepatocellular cancer (3, 6, 7). MYC induces LIN28B expression in multiple tumor models by binding to the LIN28B promoter (5).…”
Section: Introductionmentioning
confidence: 99%
“…High OCT4 expression also predicts unfavorable clinical outcome in medulloblastoma and gastric cancer [9,10]. Lin28b, an RNA-binding protein, has been implicated in the genesis of Wilms tumor [11] and gliomas [12], as well as recurrence of hepatocellular carcinoma [13], and aggressiveness of breast carcinoma [14]. Altogether, these and other recent studies highlight a contribution of pluripotency-related genes toward a more aggressive tumor phenotype, supporting their involvement in the acquisition of a stem-like state in cancer cells.…”
Section: Introductionmentioning
confidence: 99%